2012
DOI: 10.3109/13625187.2012.702810
|View full text |Cite
|
Sign up to set email alerts
|

Social and ethical determinants of sexuality: 4. Sexuality and families

Abstract: Human sexuality has moved away from having a purely reproductive function, but remains a powerful bond keeping families together, irrespective of the gender identity and the biological links of their members. Even among traditional societies, different types of families exist and the situation has become more complex as technical developments have made parenthood possible for people who in the past were excluded from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…Female sexuality and sexual relations also depend heavily on the mores of each era and society. [3][4][5][6] A Brazilian survey showed that 49% of women experience sexual dysfunction, and hypoactive sexual desire is the most prevalent disorder. 7 Paradoxically, the discussion of sexuality with doctors is limited, 8 both because of perceived taboos 9,10 and because most residents in Obstetrics and Gynecology (Ob-Gyn) are poorly equipped to address sexual problems.…”
Section: Introductionmentioning
confidence: 99%
“…Female sexuality and sexual relations also depend heavily on the mores of each era and society. [3][4][5][6] A Brazilian survey showed that 49% of women experience sexual dysfunction, and hypoactive sexual desire is the most prevalent disorder. 7 Paradoxically, the discussion of sexuality with doctors is limited, 8 both because of perceived taboos 9,10 and because most residents in Obstetrics and Gynecology (Ob-Gyn) are poorly equipped to address sexual problems.…”
Section: Introductionmentioning
confidence: 99%
“…The sexual identity and self-esteem of women is closely linked with their reproductive capability. This relationship is reinforced by social expectations concerning the female role [1]. The feeling of incapacity to fulfill their socially accepted function, which encompasses menstruation, sexual relations and motherhood, is seriously damaging to the self-image of females.…”
Section: Introductionmentioning
confidence: 99%
“…Segundo a Neuroendocrinologia, a função sexual é um fenômeno biopsicossocial complexo no qual estímulos internos e externos são modulados pelo sistema nervoso central e periférico, resultando em uma cascata de alterações bioquímicas, hormonais e circulatórias que culminam no resultado sexual físico e cognitivo 1,2 . É um fenômeno que envolve aspectos bioló-gicos, psicológicos e sociológicos 3 . Na atualidade, o comportamento sexual humano transcendeu o aspecto reprodutivo e passou a ser considerado parte integral da qualidade de vida 4,5 .…”
Section: Introductionunclassified